(untitled) (CIPEEX, 2025)
The Pediatric Intensive Care Unit (PICU) is the hospital unit responsible for special and intensive care for patients aged 0 to 18 years. It is a critical sector due to the age of the patients and the emotional weight of family members and companions, who seek humane care. The objective of this study was to evaluate the communication established by the hospital team with the parents of children admitted to Pediatric Intensive Care Units. This is an analytical, observational, qualitative, quantitative, and cross-sectional study conducted from October 2023 to March 2024 with 30 parents of children admitted to the Pediatric Intensive Care Unit of the Santa Casa Anápolis Hospital. Data were collected through a sociodemographic questionnaire and another questionnaire to assess communication by the hospital staff, both developed by the research team. Most of the participants were mothers (80%) who visited their children every day and spent most of the day at the hospital. Regarding satisfaction with communication in general at the institution, 18 participants (60%) gave the highest rating. Also, the majority (60%) reported that the doctor was primarily responsible for communication. Communication proves to be a necessary and useful tool for humanizing care in the context analyzed. Communication at Santa Casa de Anápolis was satisfactory, with professionals communicating satisfactorily and answering the questions of parents of children admitted to the ICU. In this sense, it is essential that communication and humanization in care are always promoted in order to ensure quality care.